GE_GERICHTE P/7373/2021 vom 9. Juni 2021 - GE Cour de justice (2021)
INFRACTIONS CONTRE L'HONNEUR;DIFFAMATION;PREUVES LIBERATOIRES;PREUVE DE LA VÉRITÉ;PRÉSOMPTION D'INNOCENCE;ORDONNANCE DE NON-ENTRÉE EN MATIÈRE | CP.173; CP.174; CPP.310.al1.leta